Assessing challenges and facilitators to the adoption of digital payment gateway systems in Sri Lanka: a comparative analysis with global trends - Sharangan, S.; Dilogini, S. (Technological Advances in Science, Medicine and Engineering, 2024)
Purpose: This study assesses the adoption challenges and facilitators of digital payment gateway systems in Sri Lanka, providing a comparative study with global trends. The aim is to equip stakeholders with practical recommendations to promote the adoption of digital payment systems in developing countries like Sri Lanka. Design/Methodology/Approach: This study uses a comparative analysis method to investigate areas where the transition from cash-based to digital payment gateway systems has faced challenges. A mixed-methods study design is used, combining data from 265 consumer surveys of twenty- to twenty-five-year-old Sri Lankan undergraduate students for quantitative descriptive analysis and in-depth interviews with 35 customers with at-least five years of digital payment experiences for qualitative thematic analysis. Purposive sampling methods are employed to develop a comprehensive understanding of the digital payment landscape. Findings: The study identifies several significant challenges to the adoption of digital payment systems in Sri Lanka. Firstly, there is a widespread preference for cash transactions due to higher trust levels compared to digital transactions. Secondly, a lack of digital literacy and awareness hinders the adoption of digital payment systems. Thirdly, many individuals are unbanked or underbanked, lacking access to essential banking services, credit, or debit cards. Additionally, the prevalence of informal or small-scale business activities fosters a preference for cash due to its ease of use for daily cash flows. Moreover, Cash on Delivery (COD) is preferred as it allows consumers to inspect products before paying, providing a sense of control. Lastly, digital payment providers and e-commerce platforms fail to offer sufficient incentives, such as discounts or cashback, to encourage consumers to switch from COD to digital payments. Originality/Value: This research provides novel insights by contextualizing global trends in digital payment adoption to the specific socio-economic and infrastructural conditions of Sri Lanka. It offers a nuanced understanding of local challenges and proposes tailored solutions, enhancing the relevance and applicability of the findings. Both quantitative and qualitative methods reveal consistent results, reinforcing the value of the study. Practical Implications: To address the challenges and facilitators to the adoption of digital payment gateway systems in Sri Lanka, it is recommended to clearly communicate security measures to build customer trust and provide accessible and responsive customer service to address any concerns or issues. Encouraging referrals from existing users by offering incentives for successful referrals is also crucial. Additionally, ensuring low transaction fees can make digital payments more attractive compared to traditional methods. Highlighting stories of individuals and businesses that have successfully adopted digital payments and benefited from them can promote adoption. Finally, implementing easy-to-use feedback mechanisms to gather user insights and promptly address issues will enhance user experience and trust. These recommendations align with global trends and can be adapted to the local context of Sri Lanka.
Keywords: Cash on delivery (COD); Digital payment systems; Global trends; Mixed-methods study; Sri Lanka